Inconsistency in Abnormal Functional Connectivity Across Datasets of ADHD-200 in Children With Attention Deficit Hyperactivity Disorder - Zhou, Zhi-Wei; Fang, Yan-Tong; Lan, Xia-Qing; Sun, Li; Cao, Qing-Jiu; Wang, Yu-Feng; Luo, Hong; Zang, Yu-Feng; Zhang, Hang (Frontiers in Psychiatry, 2019)
Many studies have shown abnormal functional connectivity in children with attention deficit hyperactivity disorder (ADHD) by using resting-state functional magnetic resonance imaging (rs-fMRI). However, few studies illustrated that to what extent these findings were consistent across different datasets. The present study aimed to assess the consistency of abnormal functional connectivity in children with ADHD across the 4 datasets from a public-assess rs-fMRI ADHD cohort, namely ADHD-200. We employed the identical analysis process of previous studies and examined a few factors, including connectivity with the seed regions of dorsal anterior cingulate cortex, right inferior frontal gyrus and right middle frontal gyrus; connectivity between default mode network and task positive network; stringent and lenient statistical thresholds, and the ADHD subtypes. Our results revealed a high inconsistency of abnormal seed-based connectivity in children with ADHD across all datasets, even across 3 datasets from the same research site. This inconsistency could also be observed in a lenient statistical threshold. Besides, each dataset did not show abnormal connectivity between default mode network and task positive network for ADHD, albeit this abnormal connectivity between networks was intensively reported in previous studies. Importantly, the ADHD combined subtype showed greater consistency than the inattention subtype. These findings provided methodological insights into the studies on spontaneous brain activity of ADHD, and the ADHD subtypes deserve more attention in future studies.